2019
DOI: 10.1136/bjsports-2018-100451
|View full text |Cite
|
Sign up to set email alerts
|

Copenhagen Consensus statement 2019: physical activity and ageing

Abstract: From 19th to 22nd November 2018, 26 researchers representing nine countries and a variety of academic disciplines met in Snekkersten, Denmark, to reach evidence-based consensus about physical activity and older adults. It was recognised that the term ‘older adults’ represents a highly heterogeneous population. It encompasses those that remain highly active and healthy throughout the life-course with a high intrinsic capacity to the very old and frail with low intrinsic capacity. The consensus is drawn from a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
0
12

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(155 citation statements)
references
References 0 publications
6
137
0
12
Order By: Relevance
“…According to the Copenhagen Consensus statement (2019) that considers PA and aging, researchers determined that self-efficacy, intentions, and the perceptions of one's health are related to the person's level of PA and interventions based on the theory that behavioural changes provides greater results. According to this account, they concluded that future research should assess the potential of these factors to promote PA and the good health of seniors [41].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Copenhagen Consensus statement (2019) that considers PA and aging, researchers determined that self-efficacy, intentions, and the perceptions of one's health are related to the person's level of PA and interventions based on the theory that behavioural changes provides greater results. According to this account, they concluded that future research should assess the potential of these factors to promote PA and the good health of seniors [41].…”
Section: Discussionmentioning
confidence: 99%
“…The bene ts of physical activity for slowing the ageing process and improving quality and length of life are well-known (Bangsbo et al, 2019), yet > 25% of adults 55-64y in England report fewer than 30 minutes per week at health-improving moderate-vigorous intensity. The percentage inactive rises to almost 70% for those aged 85+ (Sport England, 2019).…”
Section: Background and Rationalementioning
confidence: 99%
“…This notion and is based upon almost irrefutable evidence that regular participation in physical activity has physiological health benefits (e.g. Bangsbo et al, 2019;Blair, Cheng, & Holder, 2001;Sallis, 2009;Warburton, Nicol, & Bredin, 2006). Although less conclusive, evidence also suggests that regular physical activity can also be beneficial for participants' psychological health and wellbeing (e.g.…”
Section: Editorialmentioning
confidence: 99%